Detection of viable myocardium: comparison of dobutamine echocardiography and echocardiography after hyperbaric oxygenation - Veselka, J; Mates, M; Dolezal, V (Undersea & hyperbaric medicine, 1999)
The study concerned the possibility of using echocardiography after hyperbaric oxygenation (HBO2) to detect viable myocardium. Results were compared with dobutamine stress echocardiography (DSE). Seventeen patients with left ventricular dysfunction were enrolled in this study. The regional wall motion of the left ventricle was assessed for every patient and a wall motion score index was calculated. A resting wall motion abnormality was found in 204 segments (75%), of which 119 segments (58%) improved during DSE, and 59 (29%) after HBO2. Of 119 segments with evidence of viability in DSE, HBO2 showed viability in 58 segments. Of 85 segments non-viable in DSE, 84 segments were also non-viable after HBO2. The positive and negative predictive values of HBO2 compared to DSE were 98 and 58%, respectively. Comparing the wall motion score index at rest with the index after DSE 5 and 10 micrograms.kg-1.min-1 dobutamine and after HBO2, there was significant improvement (P < 0.005). Differences between DSE 5 micrograms.kg-1.min-1 dobutamine and DSE 10 micrograms.kg-1.min-1 dobutamine and between HBO2 and DSE 10 micrograms.kg-1.min-1 dobutamine were also significant (P < 0.005). There was no significant difference between DSE 5 micrograms.kg-1.min-1 and HBO2. Echocardiography after HBO2 is a new method for the detection of viable myocardium. It appears similar in accuracy to DSE 5 micrograms.kg-1.min-1, but is inferior to DSE 10 micrograms.kg-1.min-1.
Keywords: Ventricular Dysfunction, Left; Humans; lidé středního věku; Middle Aged; dobutamin; Myocardial Contraction; Sensitivity and Specificity; mužské pohlaví; Cardiotonic Agents; echokardiografie; Hyperbaric Oxygenation; Myocardial Infarction; ženské pohlaví; Echocardiography; hyperbarická oxygenace; infarkt myokardu; Exercise Test; zátěžový test; lidé; senzitivita a specificita; dysfunkce levé srdeční komory; Male; Dobutamine; kontrakce myokardu; kardiotonika; Female